Teori TPACK Dalam Pengembangan Bahan Ajar Pendidikan Agama Islam (PAI) - Inayati, Mahfida; Quraisy, Sherly; Muhammad, Muhammad; Zainab, Nurul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2023)
The rapid development of technology, requires teachers to update and upgrade various knowledge and understanding of learning, to suit the development of society, the characteristics of students, the development of science and technolog. TPACK is a teacher's ability that makes it easier for students to understand Islamic religious education learning during the teaching and learning process. The components in the TPACK Approach are CK, PK, TK, TPK (technological pedagogical knowledge), TCK (technological content knowledge), PCK (pendagogical content knowledge) and TPACK (technological pedagogical content knowledge). The TPACK framework is technology-based learning and is supported by pedagogical skills and mastery of material by teachers. The implementation of TPACK (Technological Pedagogical and Content Knowledge) in teaching resources and materials can make students better understand abstract concepts, avoid misconceptions, and practice high-level skills.